Epidemiological survey of early childhood caries in Cambodia - Turton, Bathsheba (BMC Oral Health, 2019)
BACKGROUND: The Southeast Asian Forum for Early Childhood Caries identified the need for more epidemiological surveys involving preschool children. To date, the only data on Early Childhood Caries in Cambodia come from convenience samples and only using the basic dmft index without measurement of the early signs of disease. METHODS: A cross-sectional survey on an epidemiological sample of Cambodian preschool children was conducted in conjunction with the fourth follow-up of the Cambodian Health and Nutrition Monitoring Study. Children were examined in a field setting using both the South East Asian Index for Early Childhood Caries as well as the ‘pulpally involved, ulcerated, fistula, abscess’ (pufa) index. Caregivers also participated in a short questionnaire covering dietary habits, oral health knowledge and behaviors, as well as the Family Impact Scale (FIS) for Oral-Health-Related Quality-of-Life. RESULTS: The sample included 3985 participants between birth and 4-years of age, across three provinces. There was an even sex distribution (50.7% male). Overall 56.6% of participants had one or more carious lesions and 5.4% had one or more pulpally-involved teeth. There were some significant differences by age and location. Among those in the 3-year-old age group 84.9% had at least one decayed tooth, and 16.1% had one or more pulpally-involved teeth. There were differences in oral health knowledge and behaviors by province; those in Phnom Penh reported more favorable responses. Consumption of non-nutritious foods also differed between provinces with those in Phnom Penh consuming a higher mean number of sweet beverages per day. Those children with at least one pulpally involved tooth had a ten times greater chance of realizing an impact across the FIS. CONCLUSIONS: Cambodian preschool children have a severe burden of dental caries and a high proportion of families are impacted by this problem. There were differences in oral health knowledge and behaviors according to province and this translated into differences in caries experience. The data from this study support the need for urgent action to address the issue of ECC in Cambodia.